Pengaruh Kualitas Pelayanan, Persepsi Kemudahan dan Kepuasan Nasabah Terhadap Keputusan Bertransaksi (Studi Kasus : Agen Brilink Di Kecamatan Bulakamba) - Kholil Rokhmat; Akbar Nuur Purnama Dharma Wahana; Slamet Bambang Riono (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This study was conducted to find out whether there is an influence of service quality, the influence of convenience perception, the influence of customer satisfaction, and the influence of service quality on transaction decisions, and also whether there is an influence of convenience perception and customer satisfaction simultaneously on transaction decisions at BRILink agents in Bulakamba District. The research method used was quantitative with multiple regression data analysis techniques, and the population was the entire community of Bulakamba District as many as 181,758 and a sample of 100 respondents. The results of this study are the significance value (Sig) of the service quality variable of 0.096, the perception of convenience 0.000 and customer satisfaction of 0.000 compared to the test value of 0.05, which means that there is an individual influence between the service quality variables but not significant, the perception of convenience and customer satisfaction significantly on transaction decisions. The F value of the table is 51,128 > out of F calculated 3,936, so the quality of service, perception of convenience and customer satisfaction together have a positive effect on consumer satisfaction. The ability of service quality, perception of convenience and customer satisfaction in influencing purchasing decisions at BRILink agents in Bulakamba District was 60.80%, while the remaining 39.20% was explained by other variables.